ECC Based Encryption for the Secured Proactive Network Forensic Framework - A, Abirami; S. , Palanikumar (Iraqi Journal of Science, 2024)
Elliptic Curve Cryptography (ECC) is one of the public key cryptosystems that works based on the algebraic models in the form of elliptic curves. Usually, in ECC to implement the encryption, the encoding of data must be carried out on the elliptic curve, which seems to be a preprocessing step. Similarly, after the decryption a post processing step must be conducted for mapping or decoding the corresponding data to the exact point on the elliptic curves. The Memory Mapping (MM) and Koblitz Encoding (KE) are the commonly used encoding models. But both encoding models have drawbacks as the MM needs more memory for processing and the KE needs more computational resources. To overcome these issues the proposed enhanced Koblitz encoding technique is used with the ECC for enhancing the security. The proposed model was compared to the existing model and found to be more efficient in terms of security. The proposed model ensure confidentiality with the encryption technique, Integrity by using the Hashing method, and authenticity and non-repudiationwith the utilization of digital signature.